Hi-CEP Project Student Worksheet Increases Social Life Skills, Entrepreneurial Interest, and Learning Outcomes (Journal of Innovative Science Education, 2019)
Student worksheet (LKPD) available in schools generally contain a summary of material, practice questions, and practical instructions that do not guide students in making the chemoentrepreneurship (CEP) project. This study aims to determine the effectiveness of the Hi-CEP LKPD project towards: SLS, entrepreneurial interests, and student learning outcomes. The benefits of this study were knowing the improvement of SLS, entrepreneurial interests, and student learning outcomes after the Hi-CEP LKPD project was implemented in project-based learning activities. The research design used was pre-test and post-test control group design. Data retrieval is done by observation, documentation, questionnaires, and tests. The SLS t value and entrepreneur interest questionnaire values ​​are -6.111 and -6.162 ≤ t table 1.667, then the experimental class has a significant change in the control class. SLS assessment and entrepreneurial interest questionnaire each have a p-value Sig. ≤ 0.05, and the Sig. (2-tailed) cognitive learning outcomes data amounted to 0.021, 0.05, then the experimental class and the control class had significant differences. The conclusion of this study is the Hi-CEP Project LKPD effectively improves social life skills, entrepreneurial interests and student learning outcomes. The researcher suggested that the teacher be able to compile the CEP project-based LKPD. The chemoentrepreneurship project (CEP) practicum can foster the entrepreneurial interest of students that is useful for the lives of students after graduating later because not all students can continue to college, besides that it can improve the social life skills (SLS) of students who appear in preparation activities manufacture of products to marketing.